2014
DOI: 10.1016/j.bbr.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the neural underpinning of perceiving and appreciating the beauty of the body

Abstract: Abstract:Although previous studies have suggested a certain degree of right hemisphere dominance for the response of extrastriate body area (EBA) during body perception, recent evidence suggests that this functional lateralization may differ between men and women. It is unknown, however, whether and how gender differences in body perception affect appreciating the beauty of the body conspecifics. Here, we applied five 10-Hz repetitive transcranial magnetic stimulation (rTMS) pulses over left and right EBA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
51
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 55 publications
5
51
1
Order By: Relevance
“…However, the relative contribution of the two areas should vary according to the model's gender. Based on previous findings (Cazzato et al, 2014), we expected that EBA-rTMS should modulate the aesthetic preference of different-, but not same-gender bodies. No specific hypothesis regarding the direction of the effects of dPMC could be made on the basis of previous studies, although the embodiment perspective on body aesthetic perception (Cross & Ticini, 2012;Ticini et al, 2015) would claim that the involvement of dPMC should be greater for those bodies that are more similar to the observer (i.e., same-gender models).…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…However, the relative contribution of the two areas should vary according to the model's gender. Based on previous findings (Cazzato et al, 2014), we expected that EBA-rTMS should modulate the aesthetic preference of different-, but not same-gender bodies. No specific hypothesis regarding the direction of the effects of dPMC could be made on the basis of previous studies, although the embodiment perspective on body aesthetic perception (Cross & Ticini, 2012;Ticini et al, 2015) would claim that the involvement of dPMC should be greater for those bodies that are more similar to the observer (i.e., same-gender models).…”
Section: Introductionmentioning
confidence: 86%
“…No study, however, has so far tested whether motor body representation may play different roles for the aesthetic appreciation of same-and different-gender bodies. While both Calvo-Merino et al (2010)'s andCazzato et al (2014)'s studies supported a necessary role of EBA in aesthetic body appreciation, to our best knowledge, no study has so far provided causative evidence for the role of motor areas with these regards, thus weakening the importance of sensorimotor embodiment in perceiving and appreciating the beauty of same-and different-gender bodies. In fact, Calvo-Merino et al (2010) reported that interfering with neural activity in the ventral PMC heightened, rather than blunting aesthetic sensitivity.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations